2007
DOI: 10.1038/sj.emboj.7601531
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of T-cell specificity and activation by the bacterial superantigen TSST-1

Abstract: Superantigens (SAGs) bind simultaneously to major histocompatibility complex (MHC) and T-cell receptor (TCR) molecules, resulting in the massive release of inflammatory cytokines that can lead to toxic shock syndrome (TSS) and death. A major causative agent of TSS is toxic shock syndrome toxin-1 (TSST-1), which is unique relative to other bacterial SAGs owing to its structural divergence and its stringent TCR specificity. Here, we report the crystal structure of TSST-1 in complex with an affinity-matured varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 49 publications
1
62
1
Order By: Relevance
“…Superantigen-mediated T cell stimulation employs regular T cell recognition synapse formation; however, recent studies have also shown that superantigens can bypass the Lck dependence of the TCR signaling pathways (45), suggesting that superantigen stimulation is an imperfect, although currently the best, experimental system to study human naive T cell responses. In particular, TSST may be the best superantigenic model because of the unique structure of the MHC-TSST-TCR complex (46). With this caveat in mind, data obtained in this system appear to be informative for T cell responses to nominal Ags.…”
Section: Discussionmentioning
confidence: 99%
“…Superantigen-mediated T cell stimulation employs regular T cell recognition synapse formation; however, recent studies have also shown that superantigens can bypass the Lck dependence of the TCR signaling pathways (45), suggesting that superantigen stimulation is an imperfect, although currently the best, experimental system to study human naive T cell responses. In particular, TSST may be the best superantigenic model because of the unique structure of the MHC-TSST-TCR complex (46). With this caveat in mind, data obtained in this system appear to be informative for T cell responses to nominal Ags.…”
Section: Discussionmentioning
confidence: 99%
“…6b). TSST-1, however, represents a third way of binding TCR by the S. aureus and S. pyogenes SAgs, using a unique TCR engagement were the TCR is tilted compared with the other SAg-TCRVβ complexes 10 . The three major contact areas between SEH and TRAV27 are the two hydrogen bonds (Asn16s-Arg69α and Ser49s-Lys56α), and the hydrophobic patch in the middle of the TCR binding cleft of SEH (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…There is currently no available structural information regarding how group III SAgs engage TCRs, which may be a consequence of the expected low affinity between the class III SAgs and the TCRs. Previous structural studies of SAgs from other classes engaging the variable β-domain of TCR (SEB, SEC 2 − 3 , SEK, TSST-1, SPE-A and SPE-C) use only the single β-chain of TCR [7][8][9][10][11] , and often, there are mutations in the TCR or SAg. To date, there is one report on structural studies of an SAg from mycoplasma (Mycoplasma arthritidis mitogen, MAM) in complex with TCR and MHC, showing specific contacts between the SAg and both variable α-domain of TCR (TCRVα) and variable β-domain of TCR (TCRVβ).…”
mentioning
confidence: 99%
“…1A). To ensure that CD4 + CD25 + CD134 + T-cell responses were not being influenced by bystander activation, we stimulated healthy donor whole blood with toxic shock syndrome toxin-1 (TSST-1) superantigen, known to interact almost exclusively with the human T-cell receptor β-chain variable domain 2.1 (TCR Vβ2) [25,26]. After 44 hours stimulation with TSST-1, the Ag-specific CD4 + CD25 + CD134 + CD39 + and CD4 + CD25 + CD134 + CD39 − T-cell populations, and the Ag non-specific CD4 + CD25 + CD134 − T-cell population, were purified by cell sorting and mRNA expression levels of the 24 common TCR Vβ families were analysed by real-time quantitative PCR (RT-qPCR).…”
Section: Resultsmentioning
confidence: 99%